Kualitas dan Potensi Dadih Sebagai Tambahan Pendapatan Peternak Kerbau di Kabupaten Kerinci - Afriani, Afriani (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2008)
An experiment was conducted to know process of production, quality and potency of curd (dadih) as source additional income of  buffalo farmer in Kabupaten Kerinci. The survey was done in three district (kecamatan) at Kabupaten Kerinci, kecamatan Air Hangat, Gunung Kerinci, and Kayu Aro. There were 28 farmer’s buffalo from 3 district that made curd. Evaluation of dadih quality was done after 3 days fermentation, include moisture content, acidity, protein, fat, and total plate count bacteria of dadih. The results showed that the farmer’s additional income was about Rp 1,787.639,97 per lactation period or total  curd  production  was  about  52.21  kg  per  lactation.  The  Curd  that made from farmer’s in three districts Kabupaten Kerinci has same quality.